(untitled) (Research, Society and Development, 2021)
The federal radial highways are all that originate in Brasília/DF and head to the ends of the country. An example of this type of highway is the BR-020, which departs from Brasília/DF and ends in Fortaleza/CE, with an extension of 2,038 km. In December 2009, the duplication of BR-020 on the stretch that connects Planaltina/DF to Formosa/GO (Km 24 to Km 58) was completed. The safety of the track, while simple, was of great concern due to the number of frontal and rear collisions between vehicles. Thus, this research aims to compare the number and types of accidents on that highway before and after the duplication of the road. For this, data obtained through the National Department of Transport Infrastructure (DNIT) and the Federal Highway Police Department (DPRF) were analyzed. After the duplication, there was a reduction in these type of accidents, however, others appeared, such as lane departure and rollover. The type of accident has been modified, but the statistics have increased substantially. It was possible to conclude that the causes of the increase in the number of accidents are related to the high speed of traffic by drivers and the number of sequential curves on the route.